The letters of Psellos : cultural networks and historical realities - Jeffreys, Michael J.; Jeffreys, Michael J.; Lauxtermann, Marc D.; Lauxtermann, Marc D. (Oxford studies in Byzantium, 2017)
'The Letters of Psellos' provides a detailed study of the correspondence of Michael Psellos, a preeminent Byzantine intellectual, politician, and writer. Structured in two parts, it juxtaposes five essays offering detailed historical and literary analyses of selected letters with annotated summaries of the entirety of Psellos' correspondence